First record of Caliothrips phaseoli Hood, 1912 (Thysanoptera: Thripidae) causing damage to forage grasses - Torres, Fabricia Z. V.; Torres, Lucas C.; Lima, Élison F. B. (Entomological Communications, 2024)
This paper reports the first record of Caliothrips phaseoli Hood, 1912 (Thysanoptera: Thripidae) causing damage to forage grasses of the species Panicum maximum in the pasture formation phase. Due to the damage observed, it is assumed that the occurrence of these insects at the beginning of the grass implementation phase can, in large infestations, reduce the photosynthetic area of ​​the plants, delaying their growth and consequently the formation of the pasture.